Current recommendations for treating autosomal dominant polycystic kidney disease. Issue 12 (December 2016) - Ness, Becky; Stovall, Kathryn
Abstract : ABSTRACT: Autosomal dominant polycystic kidney disease is the most common inherited kidney disease in the United States, causing hypertension, cerebral aneurysms, nephrolithiasis, and kidney failure. This article reviews the pathogenesis, diagnosis, associated complications, and current treatment recommendations for the condition.